Lead bioavailability in different fractions of mining- and smelting-contaminated soils based on a sequential extraction and mouse kidney model. (July 2020) - Li, Shi-Wei; Li, Meng-Ya; Sun, Hong-Jie; Li, Hong-Bo; Ma, Lena Q.
Abstract: Lead bioavailability in contaminated soils varies considerably depending on Pb speciation and sources of contamination. However, little information is available on bioavailability of Pb associated with different fractions. In this study, the Tessier sequential extraction was used to fractionate Pb in 3 contaminated soils to exchangeable (F1), carbonate-bound (F2), Fe/Mn oxides-bound (F3), organic-bound (F4), and residual fractions (F5). In addition, soil residues after F1–F2 extraction (F345 ), F1–F3 extraction (F45 ), and F1–F4 extraction (F5 ) were measured for Pb relative bioavailability (RBA) using a mouse kidney model. Based on the mouse model, Pb-RBA in the soils was 44–93%, which decreased to 43–89%, 28–75%, and 15–68% in the F345, F45, and F5 fractions, respectively. Based on Pb-RBA in the soil residues, Pb-RBA in different fractions was calculated based on a mass balance. The data showed that Pb-RBA was the highest (∼100%) in the exchangeable and carbonate fraction, and the lowest (15–68%) in the residual fraction. In addition, Pb in the first three fractions (F1–F3) contributed most (83–89%) to bioavailable Pb in contaminated soils. Our study shed light on oral bioavailability of Pb in contaminated soils of different fractions based on sequential extraction and provide important information for soil remediation. Graphical abstract: Image 10800 Highlights: Pb-contaminated soils were fractionated via sequential extraction. Relative bioavailability (RBA) of Pb in bulk and fractionated soils was measured. The Pb-RBA in each fraction was calculated based on mass balance. The Pb-RBA was highest (∼100%) in exchangeable and carbonate fraction. The Pb-RBA was lowest (14–68%) in the residual fraction. Abstract : Lead relative bioavailability in soil residues after each extraction was measured to assess Pb contribution in different fractions to bioavailable Pb in contaminated soils.